Analgesic effect of adding magnesium sulfate to epidural levobupivacaine in patients with pre-eclampsia undergoing elective cesarean section - Reem Abdelraouf Elsharkawy; Tamer Elmetwally Farahat; Mohamed Sayed Abdelhafez (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Magnesium is a physiological antagonist of NMDA receptor and a calcium channel blocker. This study was designed to test the analgesic effect of magnesium sulfate (MgSO4) when added to epidural anesthesia in mild pre-eclampsia. Material and Methods: Sixty parturients with mild pre-eclampsia were allocated randomly to two equal groups. The Placebo group received 20 ml levobupivacaine hydrochloride 0.5% plus 5 ml isotonic saline 0.9% using two separate syringes. The Magnesium group received the same amount of local anesthetic plus 5 ml of 10% MgSO4 (500 mg) using two separate syringes. The primary outcome was pain free period. While, the secondary outcomes were the onset of motor block and the time needed to achieve complete motor block. The analgesic profile was evaluated by visual analog scale (VAS) during rest or motion, the time to first request for analgesia, and the total analgesic consumption. Results: The pain-free period was significantly longer in the Magnesium group (311.3 ± 21.4) compared to placebo group (153.1 ± 22.18). The total postoperative consumption of fentanyl was significantly lower in the Magnesium group (42.4 ± 5.3) than that in the placebo group (94.4 ± 9.9), with a P value 0. 01. Both the onset time of motor block and the time needed to achieve complete motor block were significantly shorter among the Magnesium group (4.4 ± 1.4 and 8.2 ± 0.4, respectively), with a P value of 0. 01. Conclusion: The addition of 500 mg MgSO4 to epidural anesthesia fastens both sensory and motor blockade and improves postoperative analgesic profile.